Quantifying the metallurgical response of a nuclear steel to welding thermal cycles. Issue 14 (21st September 2016) - O'Meara, N.; Abdolvand, H.; Francis, J. A.; Smith, S. D.; Withers, P. J.
Abstract : Solid-state phase transformations can drastically influence the evolution of stress in welds due to the strains associated with the transformations and related changes in mechanical properties. As such, finite-element predictions of welding residual stresses need reliable materials data including, where applicable, information on phase transformation kinetics and phase- and temperature-dependent material properties. Owing to a scarcity of such data, many authors have used uncalibrated empirical modelling approaches for the prediction of welding residual stresses. This paper addresses this critical shortage for an important nuclear pressure vessel (SA508) steel. Austenite formation, grain growth and decomposition data are presented and subsequently used to calibrate transformation models. These models are shown to accurately predict microstructure and residual stresses for experimental test cases. This paper is part of a Themed Issue on Measurement, modelling and mitigation of residual stress.